Conferencias. Curso Nacional de Reproducción en Ganado de Leche. Bogotá (Colombia), 27-31 Ago 1990. - Instituto Colombiano Agropecuario, Bogotá (Colombia) (Instituto Colombiano Agropecuario, 1990)
Ganado de leche-Ganadería leche